Aktivitas Imunodulator Fraksi Etil Asetat Daun Jamblang (Syzgium cumini L) Pada Tikus Putih Jantan (Rattus norvegicus L) Yang Telah Diinfeksi Staphylococcus aureus - Muhammad Asri SR; Rudia Tamaria; Suryanita (Jurnal Kesehatan Qamarul Huda, 2024)
The immune system functions to protect the body from foreign substances such as microorganisms, bacteria, viruses and parasites. The immune system can be enhanced by administering immunomodulators. This study aims to determine the immunomodulatory activity of the jamblang leaf fraction (Syzgium cumini L) in male white rats (Rattus norvegicus L) that have been infected with Staphylococcus aureus. The extract was prepared by fractionation using ethyl acetate, ethanol, and n-hexane as solvents. Testing of immunomodulatory activity was carried out by calculating the phagocytic activity value of peritoneal macrophage cells using the Giemsa staining method with 100X magnification on a microscope. Fifteen rats tested were divided into five treatment groups, namely negative control (Na-CMC), positive control (Stimuno® 50 mg), and the extract dose group of 140 mg/kg BW, 210 mg/kg BW, 280 mg/kg BW. The treatment was given orally for 7 consecutive days and intraperitoneal injection of Staphylococcus aureus bacteria was given on day 8 for each group. The results of peritoneal fluid smear studies are used to determine the activity of macrophage cells. Data were analyzed by one way ANOVA test and followed by the HSD post hoc test. Immunomodulatory activity test showed that doses of 140 mg/kg BW, 210 mg/kg BW and 280 mg/kg BW had immunomodulatory activity by showing significant differences with the negative control and positive control groups (p<0.05). Based on the results of the study, it was shown that the immunomodulatory activity test at a dose of 280 mg/kg BW had greater immunomodulatory activity due to the greater number of activated macrophage cells.